Expert evidence: civil law, epidemiology and data quality. (5th May 2018) - Hutton, Jane L
Abstract: My experience with forensic statistics is largely through providing reports for civil cases. This article introduces the type of cases with which I have been involved, and the issues which have arisen, in a few jurisdictions. I wish to encourage more involvement, and debate on the contribution statistics might make in civil litigation, and what might be learned from criminal forensic statistics.